Tracing the Footsteps of " Minahasa Unity ": Movements of Struggle and Supporting Factors for Changes in National Insight - Dasfordate , Gamar Enno; Kurniawati (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The purpose of this article is to examine the supporting factors that caused the regional organization "Persatuan Minahasa" to change its outlook to an Indonesian national outlook during the national movement. This research uses the historical method according to Marc Bloch. There are four stages conducted in this research: problem formulation and historical observation of sources related to the Minahasa regional organization, historical criticism or data testing of the historical sources found, generalization of data in accordance with the problem under study, and search (analysis) of cause-and-effect related to the problem under study. The results of this study show how the national movement brought about a change in focus and scope, away from a regional perspective and towards the foundation of independence and popular sovereignty. Both inside and outside the Manado (Minahasa) region, Minahasan people commemorated the era by organizing their fellow citizens through regional groups throughout the Indonesian national movement. Through the ideas of Sam Ratulangi, the Union of Minahasa initiated the expansion of the Minahasan people's national outlook. In the early 20th century, both the military and intellectuals influenced the change in orientation of tribal insight to Indonesian national insight. This research shows that a deeper understanding of the transition of the Minahasan people's outlook from tribalism to nationhood is not only relevant for historical studies, but also important to inform cultural and social identity policies in the context of a multiethnic Indonesia. This research highlights that linguistic, religious and cultural diversity should be seen as a strength in building nationhood. Thus, policymakers can take a more open approach in integrating the concept of archipelagic insight, given that Indonesia's diversity can enrich national values.